2019
DOI: 10.1016/j.ijindorg.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Universal intellectual property rights: Too much of a good thing?

Abstract: Developing countries' incentives to protect intellectual property rights (IPR) are studied in a model of vertical innovation. Enforcing IPR boosts export opportunities to advanced economies but slows down technological transfers and incentives to invest in R&D. Asymmetric protection of IPR, strict in the North and lax in the South, leads in many cases to a higher world level of innovation than universal enforcement. IPR enforcement is U-shaped in the relative size of the export market compared to the domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Therefore, China's legislature should develop an IPP system that promotes technological innovation in its renewable energy industry in line with actual economic and technological development and the international environment [62,63]. While fulfilling the obligations of international conventions and safeguarding the reasonable intellectual property interests of Chinese multinational enterprises, excessive levels of intellectual property protection at the expense of social public welfare and to the detriment of national interests should be avoided [64]. Furthermore, it is important to further publicize the relevant IPP laws and basic protection paths, including in renewable energy enterprises, scientific research institutions, and higher education institutions, and to conduct IPP publicity and training for relevant staff, encouraging relevant enterprises to effectively protect their IPP through relevant laws and further improve the capacity of renewable energy IPP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, China's legislature should develop an IPP system that promotes technological innovation in its renewable energy industry in line with actual economic and technological development and the international environment [62,63]. While fulfilling the obligations of international conventions and safeguarding the reasonable intellectual property interests of Chinese multinational enterprises, excessive levels of intellectual property protection at the expense of social public welfare and to the detriment of national interests should be avoided [64]. Furthermore, it is important to further publicize the relevant IPP laws and basic protection paths, including in renewable energy enterprises, scientific research institutions, and higher education institutions, and to conduct IPP publicity and training for relevant staff, encouraging relevant enterprises to effectively protect their IPP through relevant laws and further improve the capacity of renewable energy IPP.…”
Section: Discussionmentioning
confidence: 99%
“…There is also the study of [ 11 ]. These authors found that the enforcement of intellectual property rights is positively related to increased exports to advanced economies [ 12 ], but has negative effects in developing countries, associated with reduced speed of technology transfers and incentives to invest in R&D. [ 13 ] established that rich countries and small or poor countries apply intellectual property rights for different reasons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, Branstetter et al (2006) provide empirical evidence that multinational firms transfer more technology to their foreign subsidiaries when patent laws in the receiving countries were strengthened. In a recent study, Auriol et al (2019) argue that the incentives to protect intellectual property rights differ and depend on stage of the development and the size of an emerging country. This paper provides an empirical test of the net effect of patent protection on innovation by exploiting the exogenous adoption of Prussian patent law in states that Prussia annexed in 1866.…”
Section: The Patent Controversymentioning
confidence: 99%